Topographic variability of the left atrium and pulmonary veins assessed by 3D‐CT predicts the recurrence of atrial fibrillation after catheter ablation. Issue 5 (25th April 2015) - Kiuchi, Kunihiko; Yoshida, Akihiro; Takei, Asumi; Fukuzawa, Koji; Itoh, Mitsuaki; Imamura, Kimitake; Fujiwara, Ryudo; Suzuki, Atsushi; Nakanishi, Tomoyuki; Yamashita, Soichiro; Hirata, Ken‐ichi; Kanda, Gaku; et al.
Abstract: Background: Catheter ablation (CA) is an established therapy for atrial fibrillation (AF). However, the assessment of anatomical information and predictors of AF recurrence remain unclear. We investigated the relationship between anatomical information on the left atrium (LA) and pulmonary veins (PVs) from three‐dimensional computed tomography images and the recurrence of AF after CA. Methods: Sixty‐seven consecutive AF patients (mean age: 62±10 years, median AF history: 42 (12; 60) months, mean LA size: 41±7 mm, paroxysmal: 56%) underwent CA and were followed for 19±10 months. The segmented surface areas (antral, posterior, septal, and lateral) and dimensions (between the anterior and posterior walls, the right inferior PV and mitral annulus [MA], the right superior PV and MA, the left superior PV and MA, and the mitral isthmus) of the LA were evaluated three dimensionally using the NavX system. The cross‐sectional areas of the PVs were also evaluated. Results: After the follow‐up period, 49 patients (73%) remained free from AF. A multivariate analysis showed that the diameter of the mitral isthmus and cross‐sectional area of the right upper PV were associated with AF recurrence (odds ratio: 1.070, CI: 1.02–1.12, p =0.001; odds ratio: 0.41, CI: 0.21–0.77, p =0.006). Conclusion: Enlargement of the mitral isthmus and a smaller right superior PV cross‐sectional area were associated with AF recurrence.